Increases in HPV-16/18 antibody avidity and HPV-specific memory B-cell response in mid-adult aged men post-dose three of the quadrivalent HPV vaccine. Issue 37 (31st August 2021) - Miller, Cheryl N.; Kemp, Troy J.; Abrahamsen, Martha; Isaacs-Soriano, Kimberly; Dunham, Kim; Sirak, Bradley; Pan, Yuanji; Lazcano-Ponce, Eduardo; Salmeron, Jorge; Pinto, Ligia A.; Giuliano, Anna R.
Highlights: Three doses of Gardasil induced antibody affinity maturation in mid-adult aged men. HPV-18 avidity levels correlated with anti-HPV-18 antibody levels. Gardasil induces an increase in HPV-16-specific memory B-cells. Antibody affinity maturation did not correlate with memory B-cell response. Abstract: Strong quantitative and functional antibody responses to the quadrivalent human papillomavirus (HPV) vaccine were reported in mid-adult aged men, but there are limited data on the avidity of the antibody response and the memory B-cell response following vaccination. Although circulating antibodies induced by vaccination are believed to be the main mediators of protection against infection, evaluation of avidity of antibodies and memory B cell responses are critical for a better understanding of the vaccine immunogenicity mechanisms. Both the modified enzyme-linked immunosorbent assay (ELISA) and the enzyme-linked immunosorbent spot (ELISpot) assay are tools to measure the humoral and cellular immune responses post vaccination to characterize vaccine immunogenicity. The avidity of HPV-16 and HPV-18 specific IgG in the serum of mid-adult aged men (N = 126) who received three quadrivalent HPV vaccine doses was examined using a modified ELISA. HPV-16 memory B-cell responses were assessed via ELISpot at month 0 (prior to vaccination) and 1-month post-dose three of the vaccine (month 7). The quadrivalent vaccine induced an increase in HPV-16 and HPV-18 antibody avidity at month 7. HPV-18 avidity levels moderately correlated with anti-HPV-18 antibody titers, but no association was observed for HPV-16 antibody titers and avidity levels. The HPV-16-specific memory B-cell response was induced following three vaccine doses, however, no association with anti-HPV-16 antibody avidity was observed. Three doses of quadrivalent HPV vaccine increased antibody affinity maturation for HPV-16/18 and increased the frequency of anti-HPV-16 memory B-cells in mid-adult aged men.